PENGARUH SENAM SEHAT QUR’ANI TERHADAP INSOMNIA PADA LANSIA DI BANTUL KEPEK TIMBULHARJO SEWON BANTUL YOGYAKARTA - Sri Setyowati (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2017)
Background: The age increase in the individual is a physiological process that will occur in every human, in the aging process a person will experience various problems sleep disorders or insomnia. Progressive muscle relaxation can be done by ergonomic gymnastics that conveyed by Sagiran (2013) states that ergonomic gymnastics is a movement that exercises gymnastics inspired by the movements as we perform prayers (sholat). Qur'aniHealth Gymnastic is a blend of ergonomic gymnastics with listen murottal surah ArRahman.Objective: To analyze the influence of healthy gymnastic qur'ani against insomnia in elderly in KepekTimbulharjoSewonBantul Yogyakarta.Method: This research type is quasi experiment with one group pretest-posttest design, intervention 6 times for 3 weeks done every 2 weeks. The activity begins with a pre-test of insomnia measurements using the KSPBJ-IRS questionnaire (Biology Psychiatry Study Group Jakarta-Insomnia Rating Scale). then post test week 4 to measure insomnia. A sample of 20 respondents who are active in the post yandu elderly.Results: Average Insomnia in elderly before healthy gymnastics qur 'of 13.15. and the average Insomnia in the Elderly after a healthy gymnastics qur'ani of 10.15. the difference of Insomnia in Elderly after healthy gymnastic qur'ani is statistically significant seen on t statistic value 4.908 which is bigger than t table 5% = 2.09. there is influence of difference of Insomnia to Elderly in KepekTimbulharjoSewonBantul Yogyakarta meaningful before before healthy gymnastic qur'ani with after healthy gymnastic qur'ani.Conclusion: There is influence of difference of Insomnia to Elderly in KepekTimbulharjoSewonBantul Yogyakarta that meaning between before healthy gymnastic qur'ani with after healthy gymnastic qur'ani.